STORAGE OF POTATOES AT 10-12Â°C WITH CIPC TREATMENT IN COMMERCIAL COLD STORES - Ezekiel, R; Singh, Brajesh; Kumar, Dinesh; Paul, Vijay; Das, Manish (Potato Journal, 2013)
Processing quality of potatoes was monitored during 2001-2002 in 15 commercial cold stores located in four states. Potatoes grown and stored at Indore (var. Kufri Jyoti), Ujjain (var. Kufri Lauvkar) and Deesa (var. Kufri Chandramukhi) had acceptable processing quality. Potatoes grown and stored at different parts of UP (var. Kufri Bahar) had poor processing quality.